Metode Pengusangan Cepat dengan Larutan Etanol untuk Pengujian Vigor Daya Simpan Benih Caisin (Brassica rapa L. cv. grup Caisin) - Aisa Amanah; Maryati Sari; Abdul Qadir (Jurnal Hortikultura Indonesia, 2016)
ABSTRACTThe objective of this study was to obtain effective duration in accelerated aging method with soaking the seed in 20% liquid ethanol which could estimate vigor related to storability of caisin seed during 3 and 6 months storage. There were five commercial caisin seed lots used in this study. The lots have different initial vigor. This research was conducted in two separate experiments. The first experiment was conducted to study deterioration of caisin seeds stored in aluminum foil pouches for 3 and 6 months at ambient room. The second experiment was conducted to study the effect of chemical aging duration, i.e 30, 60, 90, 120, 150, and 180 minutes moistened (12 hours imbibed) seed soaking in liquid ethanol 20%. Both of experiments were arranged in completely nested design. Germination of seeds after soaking in 20% liquid ethanol for 90 minutes was positively correlated with germination of seeds after storage for 3 and 6 months with coefficient of corellation = 0.87 and 0.88. Both coefficient of corellations were close to 1 which showed that the germination of seeds after accelerated ageing with soaking in 20% liquid ethanol could estimate seed vigor related to storability. Vigor related to storability of caisin seed after 3 months could be predicted by the equation y = 56.04+0.36x with the coefficient of determination 77.00%. While after 6 months it can be predicted by the equation y = 62.72+0.38x with the coefficient of determination 74.90%. Y variable indicates germination of caisin seed after storage while the x variable indicates germination of caisin seed after soaking in 20% liquid ethanol for 90 minutes.Key words: deterioration, devigoration, longevity, seed storage, viabilityABSTRAKPenelitian ini dilakukan untuk mendapatkan waktu perendaman ke dalam etanol 20% yang tepat pada metode pengusangan cepat kimia yang dapat menduga vigor daya simpan benih caisin setelah penyimpanan 3 dan 6 bulan. Benih yang digunakan berasal dari lima lot benih komersial dengan vigor awal yang berbeda. Penelitian terdiri atas 2 percobaan terpisah. Percobaan 1 adalah penyimpanan benih caisin dalam kemasan aluminium foil selama 3 dan 6 bulan pada ruang suhu kamar. Percobaan 2 yaitu pengusangan cepat kimia dengan merendam benih caisin yang telah dilembabkan selama 12 jam ke dalam larutan etanol 20% selama 30, 60, 90, 120, 150, dan 180 menit. Kedua percobaan menggunakan rancangan acak lengkap tersarang. Daya berkecambah benih setelah pengusangan melalui perendaman etanol 20% selama 90 menit berkorelasi positif dengan daya berkecambah benih setelah penyimpanan selama 3 dan 6 bulan. Nilai koefisien korelasi pada 3 dan 6 bulan setelah simpan adalah 0.87 dan 0.88. Kedua koefisien korelasi tersebut mendekati 1 yang menunjukkan bahwa daya berkecambah benih setelah pengusangan cepat dengan etanol 20% dapat menduga vigor daya simpan. Vigor daya simpan benih caisin setelah 3 bulan simpan dapat diduga dengan persamaan y = 62.72+0.38x dengan nilai koefisien determinasi sebesar 77.00%, sementara setelah 6 bulan dapat diduga dengan persamaan y = 56.04+0.36x dengan nilai koefisien determinasi sebesar 74.90%. Peubah y menunjukkan daya berkecambah setelah penyimpanan sedangkan x menunjukkan daya berkecambah setelah pengusangan melalui perendaman etanol 20% selama 90 menit.Kata kunci: daya simpan, deteriorasi, devigorasi, penyimpanan benih, viabilitas